Imaging of vein of Galen malformation in late trimester - Regmi, Pradeep Raj; Amatya, Isha (Journal of Patan Academy of Health Sciences, 2021)
Vein of Galen malformation is a rare congenital vascular malformation due to the maldevelopment of the embryonic precursor median vein of Markowski. It results in significant morbidity and mortality in a fetus and neonate. Fetal ultrasound plays an important role in prenatal screening of fetuses to rule out development anomalies. Fetal Magnetic Resonance Imaging (MRI) plays a dual role both in diagnosis and periodical follow-up with identification of prognostically important complications of vein of Galen malformation. The combination of fetal ultrasound and fetal MRI provides a definite diagnosis during pregnancy thereby providing an opportunity to plan the delivery of the fetus and subsequent postnatal treatment. We are presenting a case of a 34 y female presented at 35 w period of gestation to the ultrasound unit of our hospital.